Analysis of Bioinformatic algorithms for MSA - Díaz, Adrián (2023)
Aligning three or more biological sequences, such as DNA, RNA, or protein, is known as multiple sequence alignment (MSA). MSA is crucial in identifying important information about the sequences, including function, evolution, and structure. It serves as the first step in analyzing phylogenetic, protein, and genomic data. However, as sequence scale increases and the demand for alignment accuracy grows, MSA faces new challenges. Therefore, developing an efficient and precise tool for MSA and comparing its performance with existing ones has become a research hotspot in Bioinformatics. In this magister thesis, we propose a metaheuristic algorithm to solve MSA and a methodology to compare the performance of algorithms for aligning multiple sequences.